The geological history and hazards of a long-lived stratovolcano, Mt. Taranaki, New Zealand - Cronin SJ; Zernack AV; Ukstins IA; Turner MB; Torres-Orozco R; Stewart RB; Smith IEM; Procter JN; Price R; Platz T; Petterson M; Neall VE; et al. (Taylor and Francis Group on behalf of the Royal Society of New Zealand, 2021)
Mt. Taranaki is an andesitic stratovolcano in the western North Island of New Zealand. Its magmas show slab-dehydration signatures and over the last 200 kyr they show gradually increasing incompatible element concentrations. Source basaltic melts from the upper mantle lithosphere pond at the base of the crust (∼25 km), interacting with other stalled melts rich in amphibole. Evolved hydrous magmas rise and pause in the mid crust (14–6 km), before taking separate pathways to eruption. Over 228 tephras erupted over the last 30 kyr display a 1000–1500 yr-periodic cycle with a five-fold variation in eruption frequency. Magmatic supply and/or tectonic regime could control this rate-variability. The volcano has collapsed and re-grown 16 times, producing large (2 to >7.5 km3) debris avalanches. Magma intrusion along N-S striking faults below the edifice are the most likely trigger for its failure. The largest Mt. Taranaki Plinian eruption columns reach ∼27 km high, dispersing 0.1 to 0.6 km3 falls throughout the North Island. Smaller explosive eruptions, or dome-growth and collapse episodes were more frequent. Block-and-ash flows reached up to 13 km from the vent, while the largest pumice pyroclastic density currents travelled >23 km. Mt. Taranaki last erupted in AD1790 and the present annual probability of eruption is 1–1.3%.
Keywords: Taranaki; andesite stratovolcano; volcanic hazard; debris avalanche; block and ash flow; Egmont